Challenges and the Path Forward on Malaria Elimination Intervention: A Systematic Review - Khandan SHAHANDEH; Hamid Reza BASSERI (Tehran University of Medical Sciences, 2019)
Background: This systematic review was conducted to highlights key challenges, and outlines important next steps to maximize the potential to contribute to the broader malaria elimination interventions. Methods: This systematic review on malaria elimination intervention and challenges was undertaken searching six databases, between 1995 and 2018. Inclusion and exclusion criteria were set. The references were collated and categorized according to type of study, intervention, population, and health outcome. Articles selection based on title and abstract, retrieval of full text and additions of articles from reference lists and recommendations from experts. Disagreement in data extraction was solved by consultation of third reviewer. Results: Overall, 4039 records were examined related to malaria elimination that initially identified by our designated electronic databases search. Overall, 35 studies contained 14 experimental studies (40%) and 21 analytic observational studies (60%) met the inclusion criteria for this review. Studies used a wide variety of malaria elimination interventions. Types of interventions either elimination-focused interventions or general interventions on educational, prevention and treatment of malaria are included. This review pointed out the variety of challenges for eliminate malaria among low and high endemic countries. Conclusion: Malaria elimination is facilitated by strong health systems, determined leadership, appropriate incentivization, an effective surveillance system, and regional collaborations. We have identified areas for elimination-specific interventions deserve more attention in the conduct and reporting.